The “Vulnerability” Discourse in Times of Covid-19: Between Abandonment and Protection of Canadian Francophone Older Adults - Lagacé, Martine; Doucet, Amélie; Dangoisse, Pascale; Bergeron, Caroline D. (Frontiers in Public Health, 2021)
The Covid-19 pandemic has been particularly difficult for older Canadians who have experienced age discrimination. As the media can provide a powerful channel for conveying stereotypes, the current study aimed to explore how Canadian Francophone older adults and the aging process were depicted by the media during the first wave of the Covid-19 pandemic, and to examine if and how the media discourse contributed to ageist attitudes and behaviors. A content analysis of two French Canadian media op-eds and comment pieces (n = 85) published over the course of the first wave of the pandemic was conducted. Findings reveal that the aging process was mainly associated with words of decline, loss, and vulnerability. More so, older people were quasi-absent if not silent in the media discourse. Older adults were positioned as people to fight for and not as people to fight along with in the face of the pandemic. The findings from this study enhance the understanding of theories and concepts of the Theory of Social Representations and the Stereotype Content Model while outlining the importance of providing older people with a voice and a place in the shaping of public discourse around aging. Results also illustrate the transversality and influence of ageism in this linguistic minority context.